2011
DOI: 10.1016/j.juro.2011.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Overall and Cardiovascular Mortality After Radical Nephrectomy for Renal Cell Carcinoma 2 cm or Less

Abstract: Radical nephrectomy is associated with worse overall and cardiovascular survival compared to partial nephrectomy in patients with localized renal cell carcinoma 2 cm or less. These findings justify the widespread application of nephron sparing techniques to treat localized kidney cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 21 publications
5
43
3
3
Order By: Relevance
“…The study revealed an exponential increase in the utilization of PN, from 27% in 1998 to 66% in 2007. The study findings corroborated that RN is associated with a worst overall survival and an increased cardiovascular morbidity compared to partial nephrectomy for renal masses smaller than 2 cm [14].…”
Section: The Morbidity Of Radical Nephrectomysupporting
confidence: 79%
See 1 more Smart Citation
“…The study revealed an exponential increase in the utilization of PN, from 27% in 1998 to 66% in 2007. The study findings corroborated that RN is associated with a worst overall survival and an increased cardiovascular morbidity compared to partial nephrectomy for renal masses smaller than 2 cm [14].…”
Section: The Morbidity Of Radical Nephrectomysupporting
confidence: 79%
“…The study revealed an exponential increase in the utilization of PN, from 27% in 1998 to 66% in 2007. The study findings corroborated that RN is associated with a worst overall survival and an increased cardiovascular morbidity compared to partial nephrectomy for renal masses smaller than 2 cm [14].Current guidelines state that partial nephrectomy is an absolute indication in cases of a localized renal tumour in a patient for whom radical nephrectomy would necessitate renal dialysis [15,16]. This clinical scenario applies not only to cases of bilateral renal tumours but also to those of a unilateral renal tumour in the presence of a contralateral anatomically or functionally compromised kidney.…”
supporting
confidence: 78%
“…Using NSS has the advantage of preserving kidney function with lower cardiovascular death and morbidity (51,52,53,54) . NSS is considered the treatment of choice for localized little renal masses, (50) with oncological result comparable to Registered Nurse, and benefits of maintaining renal function and lowering cardiovascular death and morbidity (51,52,53,54) .…”
Section: C) Partial Nephrectomy or Nephron-sparing Surgery (Nss)mentioning
confidence: 99%
“…Using NSS has the advantage of preserving kidney function with lower cardiovascular death and morbidity (51,52,53,54) . NSS is considered the treatment of choice for localized little renal masses, (50) with oncological result comparable to Registered Nurse, and benefits of maintaining renal function and lowering cardiovascular death and morbidity (51,52,53,54) . Due to the fact that chronic kidney disease (CKD, glomerular filtering rate <60 mL/min/1.73 m2) is more widespread in a RCC patient, (52.54) the benefit of NSS can be appreciated in this study from Memorial-Sloan Kettering that found the incidence of new-onset CKD in patients with normal serum creatinine and two operating kidneys, who had actually gone through NSS and RN for little renal masses, to be 17% and 69%, respectively (53) .…”
Section: C) Partial Nephrectomy or Nephron-sparing Surgery (Nss)mentioning
confidence: 99%
“…Однако в последние годы происходит сме-щение парадигмы тактики лечения больных раком почки в сторону органосохраняющих операций. Это объясняется результатами ряда клинических исследо-ваний, которые показали сопоставимую выживаемость пациентов после проведения радикальной нефрэкто-мии (РНЭ) и резекции почки (РП), снижение риска хронической болезни почек и кардиоваскулярных осложнений после РП и, соответственно, увеличение общей выживаемости [4][5][6][7][8]. В клинических рекомен-дациях Европейской и Американской ассоциаций уро-логов указано, что при размере опухоли до 4 см выпол-нение РП обязательно, при размере в пределах 4-7 см -предпочтительно [9,10].…”
unclassified